Nasogastric Tube Feeding-Induced Esophageal Bezoar: Case Description - Jad A. Degheili; Mikhael G. Sebaaly; Ali H. Hallal (Case Reports in Medicine)
Background. Bezoars are well established entities causing gastrointestinal obstructions. Depending on the prominent constituent of these bezoars, the latter are divided into four subtypes: pharmacobezoars, lactobezoars, trichobezoars, and phytobezoars. Less frequently reported types of bezoars are reported including those formed secondary to nasogastric tube feeding with casein-based formulas. Case Presentation. A 69-year-old male presented following cardiac arrest postmyocardial infarction. Patient sustained anoxic brain injury after resuscitation, rendering him ventilator dependant along with nasogastric tube feeding, initially. Dislodging of the nasogastric tube at one time rendered it difficult to reinsert it, with investigation showing the presence of calcified material within the distal oesophagus, mainly composed of casein-based products secondary to enteral feeding. Conclusion. Bezoars are well known to cause gastrointestinal obstructions due to their indigestible characteristics within the alimentary tract. More rare causes of bezoars include those formed from casein-based feeding formulas administered to patients with sustained enteral feeding. Esophageal obstruction, secondary to casein-based bezoars, occurs due to multiple risk factors, especially in those necessitating intensive care. Approach in such scenarios requires a multiteam approach.